A handbook of modern Arabic historical scholarship on the ancient and medieval periods (Leiden ; Boston)
xxix, 653 sayfa
Keywords: “A Handbook of Modern Arabic Historical Scholarship on the Ancient and Medieval Periods presents 16 studies about modern Arab academic scholarship on the Ancient and Medieval Worlds covering disciplines as diverse as Assyriology and Mamluk studies as well as historiographical schools in the Arab World. This unique work is the first of its kind in any language. It is an important resource for scholars and students of the Ancient Near East and North Africa, Classical and Byzantine studies, and medieval Islamic history who would like to learn more about the work done by their colleagues in the Arab World in these fields over the last 7 decades and to benefit from Arabic secondary sources in their research. Contributors: Emad Abou-Ghazi, Al-Amin Abouseada, Youcef Aibeche, Sidi Mohammed Alaioud, Abdulhadi Alajmi, Allaoua Amara, Lotfi Ben Miled, Brahim El Kadiri Boutchich, Usama Gad, Azeddine Guessous, Fayza Haikal, Hani Hamza, Laith Hussein, Nasir al-Kaabi, Khaled Kchir, Mohammed Maraqten, Amr Omar, Abdelaziz Ramadan” --